Immune recovery in acute and chronic HIV infection and the impact of thymic stromal lymphopoietin. Issue 1 (December 2016) - Gelpi, Marco; Hartling, Hans; Thorsteinsson, Kristina; Gerstoft, Jan; Ullum, Henrik; Nielsen, Susanne
Abstract Background Symptomatic primary HIV infection is associated with an adverse prognosis, and immediate initiation of combination antiretroviral therapy (cART) is recommended. However, little is known about immunological predictors of immune recovery. Thymic Stromal Lymphopoietin (TSLP) is a cytokine that promotes CD4+ T cells homeostatic polyclonal proliferation and regulates Th17/regulatory T-cell balance, immunological functions known to be affected during primary HIV infection. The aim of this study was to describe immune recovery in primary and chronic HIV infection and possible impact of TSLP. Methods Prospective study including 100 HIV-infected individuals (primary HIV infection (N = 14), early presenters (>350 CD4+ T cells/μL, N = 42), late presenters without advanced disease (200–350 CD4+ T cells/μL, N = 24) and with advanced disease (<200 CD4+ T cells/μL, N = 20) and). Immune recovery was defined as increase in CD4+ T cells count from baseline to a given time of follow-up. Plasma TSLP was determined using ELISA and CD4+ T cell subpopulations (recent thymic emigrants, naïve and memory cells) were measured using flow cytometry at baseline and after 6, 12 and 24 months of cART. Results Immune recovery was comparable in all groups, and no differences in immune homeostasis were found between primary HIV infection and early presenters, whereas differences in absolute counts and proportions of CD4+ T cell subpopulations were found between primary HIV infection and late presenters. TSLP was elevated in primary HIV infection at baseline and after 24 months of cART. Interestingly, TSLP was negatively associated with proportion of recent thymic emigrants (correlation coefficient −0.60, p = 0.030). TSLP was not associated with immune recovery in primary HIV infection. Conclusions Immune recovery was comparable in primary and chronic HIV infection whereas differences in absolute counts and proportions of CD4+ T cell subpopulations were found between primary HIV infection and late presenters supporting early initiation of cART. Higher plasma TSLP was found in primary HIV infection, and TSLP was associated with lower thymic output, but not with immune recovery. These findings indicate a possible role of TSLP in immune homeostasis in HIV infection but do not support TSLP to affect immune recovery in primary HIV infection.